Meeting adolescents in their own environment: an opportunity to learn how to listen and communicate with young people. (4th April 2011) - Straathof, K; Chandaria, K; Thompson, S; Dunford, M; Nicholls, C; Poblete, X
Abstract : Background: Gaining communication skills with adolescents is a competency required by all paediatric trainees. Effective communication involves the ability to listen and empower adolescents to discuss and decide on sensitive or complex issues impacting on their health. Aims: To gain communication skills with adolescents by doing school health visits that provide information about the hospital and facilitate discussion on health topics and life style issues raised by young people themselves. Methods: Paediatric trainees carried out 2–3 school visits over 6 months during their child health rotation. Initially visits targeted a school for vulnerable adolescents at risk of school exclusion. Subsequently visits expanded to two mainstream schools. Workshops were discussed with schools and presented to parents and students as part of health promotion within Personal, Social, Health Education (PSHE) lessons. In pairs registrars did 45 min workshops introducing adolescents to their local paediatric team and hospital using different approaches, including a short video of the hospital. This was followed by a discussion on health and life style topics raised by the young people themselves. A self reporting semi-structured questionnaire was sent to all registrars involved to seek their views on the skills gained by participating in this project. Quantitative and qualitative analysis was carried out. Results: To date 17 paediatric registrars over 2 years have participated in these school visits. A response rate of 100% was achieved. 90% considered they had gained skills to communicate effectively with adolescents;80% felt they had better understanding of how the school environment impacts on young people (including impact of peer relationships) and 80% considered they had been provided with an opportunity to participate in health education. Trainees' comments on their individual learning were categorised into different themes. The most common theme was the increased understanding of adolescents' needs and the training value of talking to adolescents in their own 'comfort' zone. Trainees suggested ideas to improve further the educational value of the school visits. Conclusion: Paediatric trainees involved in school health workshops self-report gaining experience in competencies towards effective communication with adolescents. Trainees also considered that these school visits were a valuable learning opportunity to improve their understanding of young people's health needs.